A Proposal of Assessment for Local Government E-Participation - Mora Agudo, Leonor; Delgado Jalón, María Luisa; Navarro Heras, Emilio; Rivero Menéndez, José Ángel (Revista del CLAD Reforma y Democracia, 2017)
This work tries to demonstrate that it is possible to apply a quantifiable evaluation criterion to citizen participation initiatives using the information available on municipal web portal. We begin with a literature review in order to define the concept of Citizen Participation and its role in local administration, along with determining the appropriate contents that should be available on municipal websites. Then we go on to design an indicator to measure level of citizen participation on the websites and the subsequent testing of the websites of various cities in the world in order to verify their validity.The results obtained show comparable quantitative values in spite of the cultural, geographic and legislative differences of the cities chosen.
Keywords: Citizen Participation; Local Government; Evaluation; Index; Open Government; Access to Information